Constructing death : the sociology of dying and bereavement - Seale, Clive (Cambridge University Press, 1998)
A basic motivation for social and cultural life is the problem of death. By analysing the experiences of dying and bereaved people, as well as institutional responses to death, Clive Seale shows its importance for understanding the place of embodiment in social life. He draws on a comprehensive review of sociological, anthropological and historical studies, including his own research, to demonstrate the great variability that exists in human social constructions for managing mortality. Far from living in a 'death denying' society, dying and bereaved people in contemporary culture are often able to assert membership of an imagined community, through the narrative reconstruction of personal biography, drawing on a variety of cultural scripts emanating from medicine, psychology, the media and other sources. These insights are used to argue that the maintenance of the human social bond in the face of death is a continual resurrective practice, permeating everyday life.